2005
DOI: 10.1097/00001888-200509000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the University of California, Los Angeles/Charles R. Drew University Medical Education Program on Medical Students??? Intentions to Practice in Underserved Areas

Abstract: Training in the UCLA/Drew program was independently associated with intention to practice medicine in underserved communities, suggesting that a medical education program can have a positive effect on students' goals to practice in underserved areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 21 publications
5
41
0
Order By: Relevance
“…Nevertheless, intention to engage in a behavior is highly predictive of future engagement in that behavior, 30 and at least 1 study reported that graduates who indicated on the GQ that they intended to practice in underserved communities were more likely to actually do so. 31 The predictive validity of responses to the career intention items included in our analysis of career setting preferences and planned career involvement in research has not been established; such validity is the subject of future research.…”
Section: 29mentioning
confidence: 99%
“…Nevertheless, intention to engage in a behavior is highly predictive of future engagement in that behavior, 30 and at least 1 study reported that graduates who indicated on the GQ that they intended to practice in underserved communities were more likely to actually do so. 31 The predictive validity of responses to the career intention items included in our analysis of career setting preferences and planned career involvement in research has not been established; such validity is the subject of future research.…”
Section: 29mentioning
confidence: 99%
“…12 Therefore, we developed and evaluated an elective course on health care disparities designed to: 1) introduce incoming first year medical students to health disparities issues and improve their knowledge, skills, and attitudes, 2) help medical students to become aware of personal biases regarding racial and ethnic minorities, 3) inspire medical students to make a commitment to serve indigent populations. 13,14 This paper describes the course and analyzes changes in knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicate that Area Health Education Programs may wish to maximize their partnerships with family medical and other primary care specialty clerkship programs in effort to increase the number of medical students interested in pursuing a practice serving medically underserved patients upon graduation. Given that AHECs often work in partnerships with their community to develop clinical training programs that allow medical students to develop the skills and competencies to serve the medically underserved, the positive association between participation in an AHEC-sponsored clerkship experience and the intent to serve medically underserved falls in line with the research by Ferguson et al (2009) and Ko et al (2005)that states medical educational experiences can have a positive impact on the intent to practice after graduation. Given that there are many variables that may arise between when a medical student reports their intent to serve medically underserved patients and their eventual practice location, more follow-up research is needed to determine if the students actually end up practicing in medically underserved communities.…”
Section: Discussionmentioning
confidence: 52%
“…According to Ko et al (2005), there are several characteristics that can potentially predict whether physicians will practice in medically underserved communities, specifically those from an underrepresented minority race or ethnic background, growing up in a poor economic background, interest in MUC prior to admission to medical school, and incentives such as scholarships or loan repayment programs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation